Upaya Peningkatan Pengetahuan Siswa SMA Negeri 2 Tulang Bawang Tengah Tentang Hospitality and Tourism - Revirani, Selvie; Lefiani, Nia; Fadila, Kurnia (Program Studi Pariwisata, Fakultas Ekonomi dan Bisnis,Universitas Mataram, 2024)
SMA (High School) is the last level of secondary education that students must take before entering higher education. High school is the top level of formal secondary education in Indonesia. From now on, students will continue their higher education to be able to compete in the world of work. In this case, the Team's attention is to provide assistance regarding the introduction of Hospitality and Tourism from the Tourism Study Program because job opportunities in the tourism sector are very large. The method for implementing this activity is survey, mentoring, evaluation and completion. This activity was attended by 50 grade 11 students of SMA N 2 Tulang Bawang Tengah. This mentoring activity has great benefits for students, school principals, educators and education staff. This activity provides new knowledge and insight about hospitality and tourism so that students get great benefits for their future careers.